DEVELOPING ENGLISH READING MATERIALS FOR GRADE X STUDENTS OF INDUSTRIAL ELECTRONICS ENGINEERING STUDY PROGRAM AT SMKS NASIONAL SIDIKALANG - Sondang Cristiani Septiani Romaito; Indra Hartoyo; Morada Tetty (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
The objectives of this research is to develop appropriate reading materials for grade X by using scientific approach as learning material referring to Curriculum 2013. The method used in this research is research and development (R&D). This study is adapted the R&D model proposed by Jolly & Bolitho in Tomlinson (1998). The steps of this study were conducting needs analysis, developing the course grid, developing the first draft of the materials, validating materials, and revising the materials. The subjects of this research were the students of Industrial Electronics Engineering  department grade X of SMKS Nasional Sidikalang and workers of PT. Alam Daya Makmur. Three types of questionnaires were used to collect the data. The first questionnaire was made to obtain the data for the target situation and necessities, the second questionnaire was made to obtain the data for lacks and wants, and the third questionnaire was used to obtain the data about the appropriateness of the materials. The data of all questionnaires were analyzed quantitatively through descriptive statistics. The average score of the products is 3.58 which is in the range of 3.50<x<4.00 and can be categorized as Very Good.